PENGARUH ROA, DER, DAN LDR TERHADAP AUDIT DELAY PADA BANK TERDAFTAR DI BEI PERIODE 2020-204 - Leoni, Sihuanie Celsi; Kanivia, Aan; Dewi, Dessy Kumala (Politeknik Negeri Ambon, 2026)
Introduction: Audit delays are a common issue in the financial reporting process of public companies, particularly in the banking sector, which is characterized by complex operations and strict regulatory oversight. Delays in the publication of audited financial statements may reduce investor confidence and signal negative perceptions of corporate performance and transparency. This study aims to examine the effect of profitability (Return on Assets/ROA), solvency (Debt to Equity Ratio/DER), and liquidity (Loan to Deposit Ratio/LDR) on audit delay in banking subsector companies listed on the Bursa Efek Indonesia during the 2020–2024 period.Methods: This research employs a quantitative explanatory approach and purposive sampling, yielding 42 companies and 210 firm-year observations. Data were analyzed using SPSS version 25 with multiple linear regression.Results: The results indicate that profitability (ROA) has a negative and significant effect on audit delay, supporting H1. Solvency (DER) also shows a negative and significant effect on audit delay; however, the direction of the relationship is opposite to that predicted by the proposed hypothesis, so H2 is rejected. Liquidity (LDR) has a positive and significant effect on audit delay, supporting H3. Simultaneously, the three financial ratios significantly affect audit delay (H4 supported). The Adjusted R² value of 0.710 indicates that 71.0% of the variation in audit delay is explained by the independent variables, while the remaining 29.0% is explained by other factors outside the model.These findings contribute to the auditing literature and offer practical implications for companies, auditors, and regulators to improve the timeliness of financial reporting. Keywords: Audit Delay, Banking, Liquidity, Profitability, Solvency